Longitudinal Electroencephalography Analysis in Subacute Stroke Patients During Intervention of Brain–Computer Interface With Exoskeleton Feedback - Chen, Shugeng; Cao, Lei; Shu, Xiaokang; Wang, Hewei; Ding, Li; Wang, Shui-Hua; Jia, Jie (Frontiers in Neuroscience, 2020)
Background: Brain-computer interface (BCI) has been regarded as a newly-developing intervention in promoting motor recovery in stroke survivors. Several studies have been performed in chronic stroke to explore its clinical and sub-clinical efficacy. However, evidence in subacute stroke was poor and the longitudinal sensorimotor rhythm changes in subacute stroke after BCI with exoskeleton feedback was still unclear. Materials and methods: Fourteen stroke patients in subacute stage were recruited and randomly allocated to BCI group (n=7) and the control group (n=7). BCI training with exoskeleton feedback was applied in BCI group three times a week for 4 weeks. The Fugl-Meyer assessment of upper extremity (FMA-UE) scale was used to assess motor function improvement. BCI performance was calculated across the 12-time interventions. Sensorimotor rhythm changes were explored by event-related desynchronization (ERD) changes and topographies. Results: After one-month BCI intervention, both BCI group (p = 0.032) and the control group (p = 0.048) improved in FMA-UE scores. The BCI group (12.77%) showed larger percentage of improvement than the control group (7.14%) and more patients obtained good motor recovery in BCI group (57.1%) than the control group (28.6%). Patients with good recovery showed relatively higher online BCI performances, which were over 70%. And they showed a continuous improvement in offline BCI performance and obtained a highest value in the last 6 sessions of interventions during BCI training. While patients with poor recovery reached a platform in the first 6 session of interventions and didn’t improve any more or even showed a decrease. Patients with good recovery showed an enhanced ERD along with time change. Topographies showed that the ipsilesional hemisphere presented stronger activations after BCI intervention. Conclusions: BCI training with exoskeleton feedback was feasible in subacute stroke patients. BCI performance can be an index to evaluate the efficacy of BCI intervention. Patients presented increasingly stronger or continuously strong activations (ERD) may obtained better motor recovery.